The body and the voice. Pasolini's poems ‘said’ by the author - Silvia Martín Gutiérrez (Finzioni)
In May 1962 Pier Paolo Pasolini began recording some of his poems for the Rca Italiana record label. His participation, edited by Sergio Bardotti, begins the «Edizioni letterarie» series in which there will be collaborations with Giuseppe Ungaretti, Eugenio Montale or Salvatore Quasimodo. This project marks the turning point of the Rca in the studios of via Tiburtina and as regards contemporary Italian literature, it calls into question the possible benefits of recording the voice of poets on the written text. For Pasolini, it represents the opportunity to deal with his voice for the first time as an author-reader. But not only that, in the act of reading the tercets of the text chosen for the recording, the unpublished La Guinea, he reworks the poem by bringing this new multimedia medium closer to the modus operandi of Pasolini’s laboratory. From the following recording with Rca; the readings in the films for Rai and Rsi up to the debate held in Lecce in October 1975. In this essay we will retrace all the moments in which the poet reads his poems aloud.